PROBLEMATIKA HUKUM PENGGUNAAN TENAGA KERJA ASING DALAM UPAYA PERLINDUNGAN PEKERJA LOKAL - Besse Rabiatul Adawia; Asram A.T Jadda; Wahyu Rasyid; Hartono Hamzah; Asrul Hidayat (At-Tanwir Law Review, 2026)
Presidential Regulation Number 20 of 2018 on the Employment of Foreign Workers was enacted to promote investment and national economic growth. However, its implementation has raised various legal issues, particularly concerning the protection of local workers. This study aims to analyze the conformity of Presidential Regulation Number 20 of 2018 with Law Number 13 of 2003 on Manpower and to examine its impact on employment opportunities and career development of local workers in Indonesia. This research employs normative legal research using statutory and conceptual approaches. The findings indicate that several provisions of Presidential Regulation Number 20 of 2018 potentially conflict with the Manpower Law and the principle of the hierarchy of laws and regulations, thereby creating unequal competition between foreign workers and local workers. Furthermore, the implementation of technology and skill transfer has not been carried out optimally. This study concludes that strengthening supervision and policies for the protection of local workers is necessary to ensure justice and legal certainty within the national manpower system.